Spinal Cystic Schwannoma: A Rare Case Report (Bangladesh Journal of Neurosurgery, 2021)
Spinal cystic Schwannomas are very rare tumors and have been reported in only a few case reports in literature. Our case, Mrs. Halima, a 48-year-old female was admitted in Neurosurgery department of Dhaka Medical College Hospital with the complaints of low back pain more at night occasionally radiating to right buttock and numbness and tingling of the right lower limb for 2 years. MRI of Lumbo-sacral spine revealed a large circumscribed and well delineated intradural extramedullary space occupying lesion of iso to hypointense appearance in T1WI with ring enhancement on administration of gadolinium. Per-operative observation and post-operative histopathological examination revealed schwannoma. Contrast enhanced MRI was very important for the diagnosis of this rare type of tumor and surgical planning. Surgical removal was complete and patient was recovered uneventfully.Bang. J Neurosurgery 2021; 10(2): 223-225